Skull fracture as a risk factor of intracranial complications in minor head injuries: a prospective CT study in a series of 98 adult patients. Issue 4 (April 1988) - Servadei, F; Ciucci, G; Pagano, F; Rebucci, G G; Ariano, M; Piazza, G; Gaist, G
Abstract : Ninety eight patients admitted to hospital after a minor head injury were studied by CT. Forty seven patients had a skull fracture and 51 did not. Significantly more intracranial lesions were found in those with a fracture (16) that those without (3) (p less than 0.01). Nine of the patients with a skull fracture and positive CT were transferred to a neurosurgical department, where six underwent operation. Operation was not required in patients without a skull fracture. Head injured patients with a skull fracture should undergo CT scanning to enable early detection of an intracranial haematoma.